Analisis Keterampilan Berpikir Komputasi (Computational Thinking) Guru Biologi Pada Pembelajaran Lingkungan - Donna Karolina Br Surbakti; Topik Hidayat; Widi Purwianingsih; Ari Widodo; Bambang Supriatno (Jurnal Penelitian Pendidikan IPA, 2023)
Computational Thinking Skills are needed in learning. These skills must be owned by teachers and students with the aim that the demands contained in the curriculum can be achieved. One way that can be done is with a training program. The research objective was to determine the effect of training on the computational thinking skills of teachers and students in learning. The method used in this research is quasi-experimental research. The sampling technique used purposive sampling. The research sample consisted of 6 teachers and 167 students. The instrument used was a questionnaire in the form of a test given to the teacher and a student response questionnaire to learning. The results of data analysis regarding the questionnaire show that the teacher's computational thinking skills based on 4 indicators obtained an average percentage score of 75% (decomposition), 78% (pattern recognition), 83% (abstraction), and 77% (algorithm). To train students' computational skills, teachers usually train the following abilities: problem decomposition, usually teachers get used to giving complex problems, think algorithms, teachers apply problem-based learning, collaborative, cooperative, and project-based, pattern recognition, teachers use innovative learning media and abstract thinking, the teacher gives high-order thinking questions, and literacy and numeracy questions. And for the results of data analysis through questionnaires, students' responses to learning obtained an average value of 79%, with these results the learning process based on computational thinking skills that have been implemented is included in the interesting category